2015
DOI: 10.1093/jee/tov076
|View full text |Cite
|
Sign up to set email alerts
|

A Relative Resistance Ratio for Evaluation of Mexican Rice Borer (Lepidoptera: Crambidae) Susceptibility Among Sugarcane Cultivars

Abstract: The Mexican rice borer, Eoreuma loftini (Dyar), is a major pest of sugarcane (hybrids of Saccharum spp.) in Louisiana and Texas. Resistance to E. loftini was evaluated in 51 commercial and experimental cultivars of sugarcane, energycane (hybrids of Saccharum spp.), and sorghum [Sorghum bicolor (L.) Moench and hybrids of Sorghum spp.] in four replicated small plot field experiments from 2009 to 2012. A relative resistance ratio was developed to compare levels of susceptibility among cultivars based on the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 27 publications
0
41
0
Order By: Relevance
“…However, it is difficult to distinguish how much of this effect is caused by deterrence, low plant quality for the insect, or antibiosis (Dinardo-Miranda et al, 2012;Stout, 2013). The lack of correlation between tunnel length and larval development within the stalks indicates that once the larvae are established within the stalks, other resistance factors affect their development, as reported by Bessin et al (1990) and Wilson et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, it is difficult to distinguish how much of this effect is caused by deterrence, low plant quality for the insect, or antibiosis (Dinardo-Miranda et al, 2012;Stout, 2013). The lack of correlation between tunnel length and larval development within the stalks indicates that once the larvae are established within the stalks, other resistance factors affect their development, as reported by Bessin et al (1990) and Wilson et al (2015).…”
Section: Discussionmentioning
confidence: 99%
“…Various entomopathogens and entomogenous nematodes have been tried and they also failed under field conditions [14,34,39]. Planting resistant sugarcane cultivars is another way of protecting crop yields against pests, and some cultivars of sugarcane that offer degrees of resistance against E. loftini are becoming available and new resistance factors have been identified [14,53,63]. Although some cultural practices (e.g., plowing down sugarcane stubble in fallow fields and selecting optimal planting dates) have been suggested [14,53], they have not been implemented for E. loftini management.…”
Section: The Plantmentioning
confidence: 99%
“…The preference of E. loftini to oviposit on drought stressed sugarcane [14,53,[68][69][70] was demonstrated when a sugarcane cultivar resistant to E. loftini (L 03-371) under well-irrigated conditions was found to be susceptible under drought conditions (up to 88% bored internodes) [14,53,63,91]. Reay-Jones et al [68] reported that well-irrigated sugarcane was 44% less susceptible to E. loftini oviposition and injury to the crop was ≈60% lower than in water deficit stressed sugarcane of susceptible (e.g., LC 85-384) and resistant (e.g., HoCP 85-845) cultivars but oviposition preference and levels of injury to stalks relative to each cultivar did not change (i.e., HoCP 85-845 had 44% less injury than LCP 85-384 within each irrigation regime) [68,70].…”
Section: Water Deficit or Drought Stressmentioning
confidence: 99%
“…Eoreuma loftini injures 20% of sugarcane internodes in South Texas, incidentally providing portals for red rot, Colletotrichum falcatum Went., which breaks down sugar [20,27,28]. Larval population densities do not usually exceed one larva per sugarcane stalk in South Texas [29] but 50%–80% bored internodes were reported on some cultivars in Texas [3,4,30]. Nineteen percent bored internode injury in Texas resulted in an estimated decline in sugar yield of ≈25% [31].…”
Section: Introductionmentioning
confidence: 99%